UJI MICROTETRAZOLIUM (MTT) EKSTRAK METANOL DAUN Phaleria macrocarpa (Scheff.) Boerl TERHADAP SEL KANKER PAYUDARA MCF-7 - Hermansyah Amir; Bambang Gonggo Murcitro (ALOTROP, 2017)
This study aimed to investigate research about cytotoxicity correlation level of Phaleria macrocarpa (Scheff) Boerl also known as Mahkota dewa leaves methanol extract against  MCF-7 cell in vitroto investigate the relationship between them in the goal to investigate alternative low cost herbal medicine agents to fight breast cancer. Cytotoxicity properties of samples against MCF-7 breast cancer cell lines was performed by using the Microtetrazolium (MTT) assay against MCF-7 cell line. The correlation between concentration of crude and cytotoxic activity was interpreted by statistical analyses. The study showed that P. macrocarpa leaves extracts showed cytoxicity activity against breast cancer MCF-7 cell lines which IC50 concentration showed at 15 µg/mL  Correlation between concentration of extract and cytotoxicity property (absorbance value) were founded in weak relationship (R = 0.372, R2 = 0.138).  It could be effect of many different compounds in the P. macrocarpa  leaves methanol extracts may cause the pharmacological interactions, so lower or higher concentration will be antagonistic effect on absorbance or cell viability. Further study on its mechanism pathway on revealing against breast cancer could be explored. Furthermore, the natural product derived from P. macrocarpa leaves methanol extracts have potential use as alternative drugs against breast cancer.